Seed Borne Mycoflora of Tribal farmers’ Saved Hill Rice, Oryza sativa in Northeast of India - Singh, A. Ratankumar; Boopathi, T.; Singh, S. B.; Dutta, S. K.; Singh, L. S.; Lungmuana, Lungmuana; Saha, S.; Singh, N. H. (Indian Journal of Hill Farming, 2018)
Detection of seed borne pathogens through seed health testing is a critical step in the management of diseases for healthy crop establishment. The tribal farmers of Northeastern India saved their own rice seed which remains poor quality and act as carrier of many mycoflora that hinder seed viability and crop stand. This study was carried out to assess seeds of tribal farmers’ saved hill rice and improved varieties (twenty local landraces and four improved varieties) for their seed borne mycoflora collected from Mizoram, Northeastern India. The seeds were subjected to blotter and agar plate techniques to identify various seed borne mycoflora and their germination per cent and seed vigour index also calculated by paper towel method. A total of 21 fungi were recorded like Acremoniella sp. Alternaria tenuis, Curvularia lunata, C. oryzae, Dreschslera oryzae, Fusarium moniliforme, F. oxysporum, F. semitectum, Microdochium oryzae , Pyricularia grisea, Rhizoctonia sp,. Saracladium oryzae, Tilletia sp. Trichothesiums sp., stilaginoidea virens, Aspergillus flavus, A. niger, Penicillium sp. and Rizopus stolonifer and among these pathogen, Fusarium moniliforme was pre dominant in all tested rice samples ranging from (15-35%) and (54-82.0%) of agar plate and blotter paper method, respectively. Maipum (1317.43) and Manipur Nem (1171.76) showed the better performance in terms of seed germination and seedling vigour index. Idaw, recorded the maximum number of pathogen genera (14), least germination (45.45%) and vigour index (37.42). Tribal famers’ saved hill rice seeds are found to be more associated with seed borne mycoflora than the improved varieties.